Formylation, dicyanovinylation and tricyanovinylation on 5-alkoxy- and 5-amino-substituted-2,2´-bithiophenes - Raposo, M. Manuela M. (2003)
Several donor-acceptor-substituted bithiophenes were synthesized by functionalization of the corresponding 5-alkoxy- or 5-aminobithiophenes 1 by different methods: Vilsmeier formylation, metalation followed by reaction with DMF, direct tricyanovinylation reaction using TCNE or Knoevenagel condensation starting from the corresponding 5-formyl- derivatives of 1.